Patient blood management knowledge and practice among clinicians from seven European university hospitals: a multicentre survey. Issue 1 (29th October 2017) - Manzini, P. M.; Dall'Omo, A. M.; D'Antico, S.; Valfrè, A.; Pendry, K.; Wikman, A.; Fischer, D.; Borg‐Aquilina, D.; Laspina, S.; van Pampus, E. C. M.; van Kraaij, M.; Bruun, M. T.; et al.
Abstract : Background and Objectives: The aim of this survey was to evaluate the knowledge about Patient Blood Management (PBM) principles and practices amongst clinicians working in seven European hospitals participating in a European Blood Alliance (EBA) project. Materials and Methods: A web‐based questionnaire was sent to 4952 clinicians working in medical, surgery and anaesthesiology disciplines. The responses were analysed, and the overall results as well as a comparison between hospitals are presented. Results: A total of 788 responses (16%) were obtained. About 24% of respondents were not aware of a correlation between preoperative anaemia (POA) and perioperative morbidity and mortality. For 22%, treatment of POA was unlikely to favourably influence morbidity and mortality even before surgery with expected blood loss. More than half of clinicians did not routinely treat POA. 29%, when asked which is the best way to treat deficiency anaemia preoperatively, answered that they did not have sufficient knowledge and 5% chose to 'do nothing'. Amongst those who treated POA, 38% proposed red cell transfusion prior to surgery as treatment. Restrictive haemoglobin triggers for red blood cell transfusion, single unit policy and reduction of number and volumes of blood samples for diagnostic purposes were only marginally implemented. Conclusion: Overall, the responses indicated poor knowledge about PBM. Processes to diagnose and treat POA were not generally and homogeneously implemented. This survey should provide further impetus to implement programmes to improve knowledge and practice of PBM.